Extended Bandwidth Microstrip Circular Patch Antenna for Dual Band Applications - A. H. Majeed; K. H. Sayidmarie (International Journal of Electrical and Computer Engineering (IJECE), 2018)
This paper presents a new wideband microstrip circular patch antenna (MCPA) fed by proximity-coupled line with double-stub matching to achieve dual-band operation. Bandwidth extension is achieved by exciting higher-order modes in the circular radiating patch, and using two stubs to achieve adequate matching across the obtained two bands. The characteristics of the antenna such as reflection coefficient, impedance bandwidth, gain and radiation pattern are investigated and optimized through parametric studies using the CST Microwave Studio Suite. The antenna achieved a large relative bandwidth of 45.16% at the upper band, while the lower one has 10.3% relative bandwidth. The maximum achieved gain of the dual-band antenna in the 5.8GHz band is 4.62dBi while it is 4.85dBi in the upper band. The antenna has an overall size of 30×30×3.2mm3 corresponding to 0.58λ × 0.58 λ × 0.062 λ at the lower band of 5.8 GHz. The proposed antenna should be useful for WLAN and X-band communication systems.